1995
DOI: 10.1099/13500872-141-5-1193
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the glycerol kinase gene restore the ability of a ptsGHI mutant of Bacillus subtilis to grow on glycerol

Abstract: Although glycerol is not taken up via the phosphotransferase system (PTS) in Bacillus subtilis, some mutations that affect the general components of the PTS impair the ability of cells to grow on glycerol. Five revertants of a pb deletion mutant that grow on glycerol were analysed. They were shown to carry mutations in the glycerol kinase gene. These are missense mutations located in parts of the g/pK gene that could encode regions important for the activity of glycerol kinase. The results strongly suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The site of PEP-dependent, EI-and HPr-catalyzed phosphorylation was determined to be His-232 in GlpK of E. casseliflavus (109) and His-230 in GlpK of B. subtilis (158). Interestingly, in one of the B. subtilis suppressor mutants that were able to grow on glycerol despite the absence of active EI and HPr, His-230 of GlpK was replaced with an arginine, and in another mutant, the neighboring Phe-232 was replaced with a serine (937). These mutations were thought to cause structural changes similar to those triggered by phosphorylation, and the ability of these glpK mutants to grow on glycerol was assumed to be due to PTS-independent elevated activity of the mutant GlpKs.…”
Section: Regulation Of Glycerol Kinase By Pϳhis-hpr-mediated Phosphormentioning
confidence: 99%
See 1 more Smart Citation
“…The site of PEP-dependent, EI-and HPr-catalyzed phosphorylation was determined to be His-232 in GlpK of E. casseliflavus (109) and His-230 in GlpK of B. subtilis (158). Interestingly, in one of the B. subtilis suppressor mutants that were able to grow on glycerol despite the absence of active EI and HPr, His-230 of GlpK was replaced with an arginine, and in another mutant, the neighboring Phe-232 was replaced with a serine (937). These mutations were thought to cause structural changes similar to those triggered by phosphorylation, and the ability of these glpK mutants to grow on glycerol was assumed to be due to PTS-independent elevated activity of the mutant GlpKs.…”
Section: Regulation Of Glycerol Kinase By Pϳhis-hpr-mediated Phosphormentioning
confidence: 99%
“…Nevertheless, suppressor mutants that restored growth of a B. subtilis ptsHI mutant on glycerol have been obtained (52). They were not affected in ptsG but, rather, were affected in glpK (937), and glycerol uptake in gram-positive bacteria was therefore assumed to be regulated by an EIIA Glc -independent mechanism.…”
Section: Regulation Of Glycerol Kinase By Pϳhis-hpr-mediated Phosphormentioning
confidence: 99%
“…PTS-mediated GlpK stimulation therefore follows a longrange activation mechanism. Studies with an E. faecalis GlpK mutant protein in which the regulatory His-232 had been replaced with an arginine, which leads to a fully active enzyme without phosphorylation (46), suggested that phosphorylation induces structural rearrangements along the dimer interface that allow an optimal positioning of a crucial arginine residue (Arg-18) in the active site (47).…”
Section: Proteins Containing Their Own Pts-recognized Phosphorylationmentioning
confidence: 99%
“…Mutations that bypass this dependency were isolated and found to be in glpK, the gene encoding glycerol kinase which generates glycerol 3-phosphate, the internal inducer of the glp regulon in B. subtilis (Wehtje et al, 1995). Subsequently, direct phosphorylation of glycerol kinase by EI and HPr was demonstrated (Charrier et al, 1997).…”
Section: Pts-associated Proteinsmentioning
confidence: 99%